Perceived adherence and associated barriers to the national atopic dermatitis guideline: A survey among general practitioners - Aviël Ragamin; Karlijn F. van Halewijn; Marie L.A. Schuttelaar; Marjolein Lugtenberg; Suzanne G.M.A. Pasmans; Gijs Elshout; Renske Schappin (European Journal of General Practice, 2023)
AbstractBackground General practitioners (GPs) have an important role in managing patients with atopic dermatitis (AD). Although pivotal, adherence to dermatological guidelines in general practice has not been assessed.Objectives To assess GPs’ perceived adherence and barriers to the Dutch AD guideline.Methods A survey was conducted among 391 GPs in the Netherlands between December 2021 and May 2022. GPs rated their perceived adherence and perceived barriers concerning five key recommendations of the AD guideline, following an existing framework. The correlation between perceived adherence and barriers was investigated using Spearman’s rank correlation.Results A total of 213 GPs (54%) participated. Perceived adherence rates varied across recommendations (43.7% to 98.1%). Lowest adherence was reported for recommendations concerning topical corticosteroids (TCS). Across all recommendations, patient factors (65.6%; SD 11.6) and lack of applicability to specific patient groups (29.5%; SD 10.5) were reported most frequently as barriers. The overall correlation between adherence and barriers was strongest for knowledge (ρ .55; SD .10) and attitude-related factors (range: ρ .40--.62).Conclusion GPs’ perceived adherence and barriers vary substantially across recommendations of the AD guideline. In particular, GPs reported lower adherence to recommendations concerning TCS. Next to patient-related factors, strong correlations between adherence perceived by GPs and knowledge and attitude-related barriers suggest the importance of addressing these factors as well to improve adherence.